تأثير الروحية التنظيمية في جودة الخدمات العامة: بحث ميداني في عدد من مستشفيات دائرة صحة بغداد / الرصافة - الشيخلي، عبدالرزاق إبراهيم; رحيمة، سلمى حتيتة (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2018)
Spirituality is one of modern subjects that gained importance of their role in the significance imparted to work and to promote a sense of belonging to the group and the community. The research aims to highlight the impact of the relationship between organizational spiritual and variabl Quality of public services, to sample variant of the hospitals, health department BAGHDAD / Rusafa. And in order to achieve this, the researcher is based on the descriptive and analytical approach adopted for the analysis of the questionnaire and to test relations research and its variables. The research community (4) of hospitals in Sadr City, included've targeted 106 doctors and 222 nurses formed a whole (328) factor of the doctors and nurses of the hospitals surveyed, have been analyzing the data and test hypotheses using a number of appropriate statistical tools such as the arithmetic mean weighted and standard deviation to measure changes in the level of hospitals and the simple equation to test the impact of the decline. In the final analysis, the results showed the validity of the research main hypothesis there is the effect of organizational spiritual in the quality of public services, depending upon formulated a number of conclusions based on which a researcher in the development of a number of recommendations for hospitals surveyed, including: providing job security. And to prevent attacks on doctors and nurses through the activation of the protection of doctors and accounting aggressors law legally, and contrast enhancing behaviors ethical for doctors and nurses to deal with patients, And the need for the Department of Health in Baghdad / Rusafa prepare organizational structure of hospitals surveyed included in it, at least, if not the Department of Quality Management Vedrj the unit quality management, as it is not listed among the organizational structure of the hospitals surveyed.
تعد الروحية إحدى الموضوعات الحديثة التي اكتسبت أهميتها من دورها في إضفاء معني للعمل وتعزيز الشعور بالانتماء للجماعة وللمجتمع. يهدف البحث إلى تسليط الضوء على علاقة التأثير بين متغير الروحية التنظيمية ومتغير جودة الخدمات العامة لعينة من مستشفيات دائرة صحة بغداد/الرصافة. وسعياً لتحقيق ذلك، فقد اعتمدت الباحثة بشكل أساس على المنهج الوصفي التحليلي لتحليل الاستبانة ولاختبار علاقات البحث ومتغيراته. لقد استهدف مجتمع البحث (4) من مستشفيات مدينة الصدر، تضمنت (106) طبيب و(222) ممرضاً شكلت بمجملها (328) عاملاً من الأطباء والممرضين للمستشفيات المبحوثة، وقد جرى تحليل البيانات واختبار الفرضيات باستخدام عدد من الأدوات الإحصائية الملائمة مثل الوسط الحسابي الموزون والانحراف المعياري لقياس مستوى المتغيرات في المستشفيات ومعادلة الانحدار البسيط لاختبار التأثير. وفي المحصلة النهائية، أظهرت النتائج صحة فرضية البحث الرئيسة، وهي هناك تأثير للروحية التنظيمية في جودة الخدمات العامة، وبالاعتماد عليها صيغت عدد من الاستنتاجات التي استندت إليها الباحثة في وضع جملة من التوصيات للمستشفيات المبحوثة منها: توفير الأمان الوظيفي، ومنع الاعتداءات على الأطباء والممرضين من خلال تفعيل قانون حماية الأطباء ومحاسبة المعتدين قانونيا. وبالمقابل تعزيز السلوكيات الأخلاقية للأطباء وللممرضين في التعامل مع المرضى. وضرورة قيام دائرة صحة بغداد/الرصافة بإعداد هيكل تنظيمي للمستشفيات المبحوثة يدرج فيه على الأقل إن لم يكن قسم إدارة الجودة فيدرج فيها واحدة إدارة الجودة، إذ إنها غير مدرجة من ضمن الهيكل التنظيمي للمستشفيات المبحوثة.
Keywords: المستشفيات -- الخدمات الصحية -- الخدمات العامة -- جودة الخدمات -- الروحية التنظيمية -- دائرة صحة بغداد / الرصافة -- العراق